TECTONIC EVOLUTION VS NEOGENE MAGMATISM IN TRANS-CARPATHIANS - Shevchuk, V.; Vasylenko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The second half of XX century marked a period of intensive tectonic and geophysical research in the trans-Carpathian region, with kinematic, structural, and paragenetic analyses used. The research on the trans-Carpathian trough recorded sundry sublatitudinal and submeridional tectonic discontinuities. Previous structural and paragenetic grid analysis of multi-ordinal faults within the trans-Carpathian region and surrounding areas together with data on the distribution of magmatic centers in space and time enabled a new dynamic and kinematic scheme of Neogene tectonic and magmatic activation. According to the scheme mentioned, there evolved structural paragenesis of the shear zone because of the right shift resulting from submeridional compression within the trans-Carpathian region, common to entire Carpathian nappe system. The northern border of the shear zone is a rectilinear zone of the trans-Carpathian deep fault with north-western strike and subvertical fall. The southern border spreads along the zone of Prepannonian deep fault and the Shamos (Somes) line, where the shears got complicated, probably, because of tectonic blocks reversals. This scheme explains the formation of volcanic foci via the formation of layered structures of tension within the designated shear zone. The mechanism of trans-Carpathian Neogene magmatism is regarded as one of the stages of Meso-Cenozoic tectonic evolution of Pannonia. When marking the stages, consideration is to be given to the presence or absence of oceanic crust within the Pannonian basin of Neotetis. According to the authors, its main substratum was a thinned suboceanic crust, which, however, does not exclude the existence of a small layer of oceanic crust. Tectonic evolution of Pannonia during Meso-Cenozoic period is put into three stages. The first stage combines subductive and obductive processes, the second one is associated with creating nappes of the Ukrainian Carpathians, and the third one, respectively, with the formation of overthrust mechanism of weakening compressional stresses, leading to the formation of the shear zone and volcanism within the trans-Carpathian trough.
Keywords: Neogene volcanism; trans-Carpathians; tectonic evolution stage; dynamic-kinematical scheme; volcanic centers